The Critical Role of the Right Uncinate Fasciculus in Emotional Empathy - Oishi, Kenichi (Ann Neurol, 2014)
OBJECTIVE: Common neurological diseases or injuries that can affect the right hemisphere, including stroke, traumatic brain injury, and frontotemporal dementia, disrupt emotional empathy – the ability to share in and make inferences about how other people feel. This impairment negatively impacts social interactions and relationships. Accumulating evidence indicates that emotional empathy depends on coordinated functions of orbitofrontal cortex, anterior insula, anterior cingulate, temporal pole, and amygdala, but few studies have investigated effects of lesions to white matter tracts that connect these structures. We tested the hypothesis that percent damage to specific white matter tracts connecting these gray matter structures predicts error rate in an emotional empathy task after acute right hemisphere ischemic stroke. METHODS: We used multivariable linear variable linear regression with percent damage to 8 white matter tracts, age, and education as independent variables and error rate on emotional empathy as the dependent variable to test a predictive model of emotional empathy in 30 patients with acute ischemic right hemisphere stroke. RESULTS: Percent damage to 8 white matter tracts along with age and education predicted the error rate in emotional empathy; but only percent damage to the uncinate fasciculus was independently associated with error rate. Participants with right uncinate fasciculus lesions were significantly more impaired than right hemisphere stroke patients without uncinate fasciculus lesions in the emotional empathy task. INTERPRETATION: The right uncinate fasciculus plays an important role in the emotional empathy network. Patients with lesions in this network should be evaluated for empathy, so deficits can be addressed.